Church and culture in seventeenth-century France - Phillips, Henry (J. Henry) (Cambridge University Press, 1997)
Church and Culture in Seventeenth-Century France brings together the social, religious and intellectual history of the Grand Siecle and focuses on the involvement of the Church in a variety of cultural domains, including literature, art, censorship and ideas. It explores the limits as well as the extent of the Church's influence, especially in its attempt to impose orthodoxy in all areas and on all sections of society. Given that orthodoxy determines the believer's inclusion or exclusion from the Church, thus implying the notion of boundaries in a context of constraint, the study is conceived according to a number of spaces. The notion of space is sometimes interpreted literally, e.g. Port-Royal, the school and the church building, and sometimes metaphorically, e.g. orthodoxy itself, science and theology. The book also deals with religious attitudes to libertinage, atheism and deism, and with aspects of French Protestantism.
Keywords: Catholic Church -- France -- History -- 17th century.; Catholic Church -- History -- 17th century.; Église catholique -- France -- Histoire -- 17e siècle.; Église catholique -- Histoire -- 17e siècle.; Catholic Church; Katholische Kirche; Christianity and culture -- France -- History -- 17th century.; France -- Civilization -- 17th century.; France -- Church history -- 17th century.; Christianisme et civilisation -- France -- Histoire -- 17e siècle.; France -- Civilisation -- 17e siècle.; France -- Histoire religieuse -- 17e siècle.; RELIGION -- Christianity -- General.; RELIGION -- Christian Life -- Social Issues.; Christianity and culture; Civilization; France; Kultur; Frankreich; Maatschappij.; Rooms-Katholieke Kerk.; Christianisme et civilisation.; Religion et culture -- France -- 18e siècle.; Église catholique -- France -- 17e siècle.; Église catholique et culture -- 17e siècle.; Katholische Kirche.; 1600-1699; Electronic books.; Church history; History